Is the Utilization of Helicobacter pylori Stool Antigen Tests Appropriate in an Urban Canadian Population?. Issue 5 (7th March 2020) - Ma, Irene; Guo, Maggie; Pillai, Dylan R; Church, Deirdre L; Naugler, Christopher
Abstract: Objectives: Helicobacter pylori stool antigen test (HpSAT) appropriateness was investigated by assessing its testing and positivity rates in Calgary, Canada. Methods: The laboratory information system was accessed for all patients who received an HpSAT in 2018. Testing volume, test results, age, and sex of patients were collected. Sociodemographic risk factors and geospatial analysis were performed by matching laboratory data to the 2016 census data. Testing appropriateness was defined as a concordance between testing and positivity rates for each sociodemographic variable. Results: In 2018, 25, 518 H pylori stool antigen tests were performed in Calgary, with an overall positivity rate of 14.7%. Geospatial mapping demonstrated significant distribution variations of testing and positivity rates of HpSAT in the city. Certain sociodemographic groups studied (eg, recent immigrants) appeared to be appropriately tested (testing rate relative risk [RR] = 2.26, positivity rate RR = 4.32; P < .0001), while other groups (eg, male) may have been undertested (testing rate RR = 0.85, positivity rate RR = 1.14; P < .0001). Conclusions: Determining concordance of testing and positivity rate of a laboratory test can be used for assessing testing appropriateness for other diseases in other jurisdictions. This study demonstrated some at-risk patients may be missed for H pylori testing.